Pengaruh Lingkungan Keluarga terhadap Prestasi Belajar Siswa di Sekolah Dasar - Najwa Putri Yunsiah Nasution; Melva Zainil (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the influence of the family environment on student learning achievement in elementary school. The family environment is an external factor that plays an important role in shaping children's character, motivation, and learning habits. This study uses a literature study method with a descriptive qualitative approach, which examines various academic literature related to the topic. The results of the study show that family harmony, parental attention and assistance, socioeconomic conditions, and parenting style have a real contribution to students' academic achievement. Families who are able to provide a positive and supportive learning environment emotionally and structurally can increase children's mental readiness and motivation in facing the learning process. These findings are also reinforced by developmental ecological theories that place the family as the closest microsystem that most early influences a child's development. Therefore, the active involvement of families in children's education needs to be strengthened as part of efforts to improve the quality of basic education.